Peer Pressure and Substance Use in Emerging Adulthood: A Latent Profile Analysis. (1st July 2020) - Keyzers, Angela; Lee, Sun-Kyung; Dworkin, Jodi
Abstract: Introduction: Peers play an important role in influencing emerging adults' substance use behaviors, however, research on peer pressure has typically not been extended beyond adolescence to include emerging adulthood. Little research has examined the relationships between various peer pressure domains and emerging adult substance use. Methods: This study used quantitative data from 359 emerging adults (aged 18-29 years, M  = 25.46 years; 60.8% female; 74.2% White) to explore the associations between different types of peer pressure (e.g. peer pressure to socialize and peer pressure to use substances) and substance use among a diverse sample of emerging adults. Latent profile analysis and path analysis were used for analysis. Results: Three unique profiles of perceived peer pressure emerged (negative peer pressure, positive peer pressure, and no perceived peer pressure). The negative peer pressure group was more likely to engage in binge drinking, lifetime alcohol use and lifetime marijuana use than the no peer pressure group. The positive peer pressure group was less likely to engage in lifetime alcohol or marijuana use compared to the no peer pressure group. Discussion: Findings suggest that peer pressure is associated with emerging adult substance use, in both negative and positive ways. Results of the current study provide the critical groundwork for more sophisticated studies seeking to understand the pathways by which positive and negative peer pressure impact emerging adult behavior.